Agar-based Biocomposites slow down Progression in the Reproductive Cycle Facilitating Synchronization of the Gonads of Reared Specimens of Paracentrotus lividus - Adele Fabbrocini; Maria Grazia Volpe; Elena Coccia; Raffaele D'Adamo; Marina Paolucci (International Journal of Aquaculture and Fishery Sciences - Peertechz Publications, 2015)
Background: Biopolymers have many fields of application. In Echiniculture they are usually employed to bind trial diets, although a systematic study on the performances of biopolymers as feed binders is lacking.                                                                                                Methods: Several biopolymers (sodium alginate, agar, gellan, apple pectin and citrus pectin with different esterification degree) were employed as binders in the manufacture of biocomposites to be used as Paracentrotus lividus feed. Biocomposites were first produced with varying percentages of feed ingredients (5-25%) and polymers (2-3%), either alone or in blends of two types. Biocomposites were tested for stability, swelling and nutrient release in water. In order to evaluate their palatability, biocomposites were administered to sea urchins and eating activity checked up to 48 h. GI and gonad composition were evaluated in a 14-week rearing trial.                                                                                         Result:Agar and apple pectin gave the best results in terms of stability, swelling and nutrient release in water and were well accepted by sea urchins. When tested in the rearing trial both biocomposites produced a slow progression in the reproductive cycle, more marked in the agar-based ones. Conclusion: This study demonstrates that agar has promising features as a binder in the formulation of diets for Paracentrotus lividus. Agar biocomposites were readily accepted by urchins, absorbed a minimal amount of water, and produced negligible waste and nutrient dispersal in the rearing system. Moreover, slower progression in the reproductive cycle facilitates synchronization of the gonads of reared specimens to the desired reproductive state. Finally, being their nutrient composition easily adjustable according to specific rearing needs, agar biocomposites are an interesting starting-point for the formulation of highly versatile prepared feed.